The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1093/ageing/aft163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of music-based multitask training on cognition and mood in older adults

Abstract: six months of once weekly music-based multitask training was associated with improved cognitive function and decreased anxiety in community-dwelling older adults, compared with non-exercising controls. Studies designed to further delineate whether training-induced changes in cognitive function could contribute to dual-task gait improvements and falls reduction, remain to be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 32 publications
1
133
1
4
Order By: Relevance
“…The effect of MT on visuospatial function was assessed in 3 studies, with 1 high female study [73] and 2 low female studies [76; 83] (3 effect sizes). MT improved performance compared to controls (g = 1.003, SE = 0.172, p < 0.000; see Figure 4C).…”
Section: Sex Differences In Exercise Efficacy On Visuospatial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of MT on visuospatial function was assessed in 3 studies, with 1 high female study [73] and 2 low female studies [76; 83] (3 effect sizes). MT improved performance compared to controls (g = 1.003, SE = 0.172, p < 0.000; see Figure 4C).…”
Section: Sex Differences In Exercise Efficacy On Visuospatial Functionmentioning
confidence: 99%
“…RT decreased global cognition compared to controls (g = -1.812, SE = 0.543, p = 0.001; see Figure 7B). Four studies (1 high female study [73], 3 low female studies [67; 77; 83]) examined the effect of MT on global cognition (4 effect sizes), and found that MT improved performance compared to controls (g = 1.801, SE = 0.199, p < 0.000; see Figure 7C). Comparisons between studies with high number of females and low number of females were not conducted for AT, RT, or MT because of the low number of studies.…”
Section: Sex Differences In Exercise Efficacy On Global Cognitive Funmentioning
confidence: 99%
“…Group singing interventions have pointed to increases in general well-being (Clift et al, 2010), self-esteem, social bonding and meaning (Cohen et al, 2006; Davidson, 2011; Tarr, Launey, & Dunbar, 2014). With older adults, interventions focused on engaging with musical instruments have provided evidence towards anxiety reduction (Hars, Herrmann, Gold, Rizzoli, & Trombetti, 2014), a sense of accomplishment (Perkins & Williamon, 2014), purpose, control, autonomy, social well-being (Creech, Hallam, Varvarigou, McQueen, & Gaunt, 2013), and increased cognitive function (Seinfeld, Figueroa, Ortiz-Gil, & Sandrez-Vives, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Existen estudios que manifiestan los beneficios de la música, por ejemplo, Hars et al (2014) para abordar su investigación, parten de que la música es beneficiosa para el entrenamiento de multitareas, incidiendo tanto en el funcionamiento cognitivo como en el estado de ánimo. En su investigación cuentan con adultos mayores a partir de los 65 años de edad.…”
Section: Otra Estrategia: Euritmiaunclassified